The effect of blended learning and digital literacy model on understanding the Sutta Piṭaka - Mujiyanto Mujiyanto; Suherman Suherman (SMARATUNGGA: JURNAL OF EDUCATION AND BUDDHIST STUDIES, 2021)
Understanding of Sutta Piṭaka is extremely important for master’s degree of Buddhist Education students. The purpose of this study is to explore how the influence of blended learning and digital literacy learning models on the understanding of Sutta Piṭaka for master’s degree of Buddhist Education students. Employing a quantitative approach with ex-post facto research methods, the sample in this study is all master’s degree of Buddhist Education students (S2) year of 2019 with a total of 36 students. The instrument used in this study is a questionnaire with a Linkert scale. The results of the validity and reliability test stated that the instrument was valid and reliable. Hypotheses were tested using regression analysis. The results showed that the blended learning model had a positive and significant effect on understanding the Sutta Piṭaka with an effective contribution of 32.88%. Digital literacy has a positive and significant effect on understanding the Sutta Piṭaka with an effective contribution of 45.51%. The blended learning and digital literacy learning models have a positive effect of 78.4% on the understanding of the Sutta Piṭaka. Based on the result, it can be said that blended learning and digital literacy give a good impact on students to gain sufficient understanding of the Sutta Piṭaka. The research contributes to the growth of science and technology in the education field, particularly maximizing the skill and knowledge using blended learning and digital literacy model on understanding the Sutta Piṭaka.